Analysis of Online Teaching Reform in Higher Education Background of Internet - Wang, Yong Jian (International Journal of Management and Education in Human Development, 2022)
At present, the development of China's higher education has rapidly entered the stage of popularization, but the classroom teaching reform in ordinary colleges and universities lags, and the attraction of traditional classrooms to students has decreased, which urgently requires the emergence of a new teaching form to change the difficulties faced by colleges and Universities. In the 13th five-year plan for the development of national education, it is pointed out that teachers are encouraged to use the Internet, big data, virtual reality technology, and other information-based means to improve teaching levels and explore new models of education and teaching in the future by constantly trying new teaching methods. Under the background of the rapid development of Internet technology, the construction and development of educational and teaching informatization in colleges and universities have been greatly promoted, and at the same time, it also promotes the integration of educational ideas and information technology. In 2020, the sudden COVID-19 epidemic prompted colleges and universities across the country to actively respond to the call of the Ministry of education to "suspend classes without suspension", and accumulated rich experience in online teaching reform. However, in the process of teaching reform, teachers' online teaching ability, students' autonomous learning ability, online teaching resources, technical support, and university management have encountered some problems. I combed the development process of teaching reform, analyzed the problems exposed in the practice of online teaching reform during the epidemic, comprehensively summarized the reasons for the problems in online teaching reform, and put forward targeted countermeasures and suggestions for online teaching reform of higher education, to further promote its teaching reform.